Stimuli‐Responsive Materials: Finite‐Element‐Based Deep‐Learning Model for Deformation Behavior of Digital Materials (Adv. Theory Simul. 7/2020). Issue 7 (3rd July 2020) - Zhang, Zhizhou; Gu, Grace X.
Abstract : Digital materials are programmable smart composites that exhibit complex deformation when experiencing external stimuli. In article number 2000031, Zhizhou Zhang and Grace X. Gu report work that integrates multi‐physics modeling and machine learning (convolutional neural networks) to accelerate the prediction of the non‐linear deformation behavior of stimuli‐responsive digital materials. Moreover, high‐level design principles can be extracted from the model using sensitivity analysis.